CODE MIXING IN ITSFIYAWIN IF I CAN’T - Desmalia Purba; Ester Veronica Anastasya Marpaung (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2019)
This study deals with “Code Mixing in Itsfiyawn If I Can’t”. This thesis was analyzed by using qualitative method and quantitative method which some references are searched that will be used as source books. The objective of this study is to know the types of code mixing, the most dominant type of code mixing and the reason of the most dominant type of code mixing at all of eighteen chapters. This study applies research based on qualitative and quantitative. The findings of this study shows that there are types of code mixing found based on the theory of Muysken. The study has been found that, there are 144 code mixing, consist of 98 occurrences for insertion (68,08%), 23 occurrences for alternation (15,96%), and 23 occurrences for congruent lexicalization (15,96%). Based on the analysis, it concludes that the most dominant type of code mixing is the insertion with 68,08% or 98 occurrences.